2019
DOI: 10.1111/ejn.14523
|View full text |Cite
|
Sign up to set email alerts
|

The role of the nucleus accumbens in learned approach behavior diminishes with training

Abstract: Nucleus accumbens dopamine plays a key role in reward‐directed approach. Past findings suggest that dopamine's role in the expression of learned behavior diminishes with extended training. However, little is known about the central substrates that mediate the shift to dopamine‐independent reward approach. In the present study, rats approached and inserted the head into a reward compartment in response to a cue signaling food delivery. On days 4 and 5 of 28‐trial‐per‐day sessions, D1 receptor antagonist R(+)‐7‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…To determine whether our behavioral predictive power was arbitrary to any population-level component, we ran the binomial regression on all major components, and found that only those containing significant context information had predictive utility during the delay period. These population-level results align with a growing body of work advocating for population-level interpretations of neural data, suggesting that certain neural computations are better understood in terms of their population-level versus single-unit output (Ebitz & Hayden, 2021;Gallego et al, 2017;Saxena & Cunningham, 2019;Vyas et al, 2020). A primary argument for this approach is that there is a high degree of correlation and redundancy across single-unit coding, suggesting that the large neural space occupied by units in a region can be captured by a drastically lower dimensional latent space.…”
Section: Relationship Between Context and Value Coding In The Nacsupporting
confidence: 75%
See 1 more Smart Citation
“…To determine whether our behavioral predictive power was arbitrary to any population-level component, we ran the binomial regression on all major components, and found that only those containing significant context information had predictive utility during the delay period. These population-level results align with a growing body of work advocating for population-level interpretations of neural data, suggesting that certain neural computations are better understood in terms of their population-level versus single-unit output (Ebitz & Hayden, 2021;Gallego et al, 2017;Saxena & Cunningham, 2019;Vyas et al, 2020). A primary argument for this approach is that there is a high degree of correlation and redundancy across single-unit coding, suggesting that the large neural space occupied by units in a region can be captured by a drastically lower dimensional latent space.…”
Section: Relationship Between Context and Value Coding In The Nacsupporting
confidence: 75%
“…However, speculatively this finding may suggest that during initial learning, the NAc receives cue information and processes it solely in terms of its motivational relevance, and some other structure is supporting context-dependent behavior, but then after extensive learning, it forms representations of the associative structure. Interestingly, recent work has suggested that motivated approach behavior becomes less NAc-dependent as training progresses (Dobrovitsky et al, 2019). Whether or not this is related to a shift in the role of the NAc as a behavior becomes learned, or related to distinct inputs such as from the hippocampus and cortex, remains to be determined.…”
Section: Context Coding In the Nacmentioning
confidence: 99%
“…However, speculatively this finding may suggest that during initial learning, the NAc receives cue information and processes it solely in terms of its motivational relevance, and some other structure is supporting context-dependent behavior, but then after extensive learning, it forms representations of the associative structure. Interestingly, recent work has suggested that motivated approach behavior becomes less NAc dependent as training progresses [ 63 ]. Whether or not this is related to a shift in the role of the NAc as a behavior becomes learned, or related to distinct inputs such as from the hippocampus and cortex, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…However, the dependence of S+-evoked excitation and behavioral performance on NMDARs was absent in overtrained animals (Fig. 4), suggesting that overtraining induces a secondary plastic change within the NAc core 47 (stage 4, Fig. 9).…”
Section: Discussionmentioning
confidence: 99%